Impediments to the process of aligning business and information systems strategies in public service organisations - Burke, Anne (Trinity College (Dublin, Ireland). Trinity Business School, 2017)
With the rise of e-business, organisations have become increasingly reliant on information systems (IS). Alignment of IS and business strategies has become a key factor in contributing to the creation of business value for organisations. The strategic alignment of business and IS strategies has been a top management concern for both IS management and business executives for over three decades. Failure to align business and IS strategies may result in misused resources and failed IS projects, culminating in negative financial and organisational outcomes. A number of scholars have tried to ascertain factors that contribute as either enablers or impediments to this process of strategic alignment.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin, 2017